Entrepreneurial Characteristics Amongst Different Professional Backgrounds: Evidence from Indonesia - Hetty Karunia Tunjungsari; Frangky Selamat; Chairy Chairy; Didi Widya Utama (Sekolah Tinggi Manajemen IPMI, 2018)
The primary objective of this study is to examine the evidence of entrepreneurial characteristics amongst different professional backgrounds, both entrepreneurs and non-entrepreneurs, especially private employees, government employees, police officers, and entrepreneurs. We examined entrepreneurial characteristics in terms of innovativeness, need for achievement, the locus of control, risk-taking propensity, tolerance for ambiguity, and self-confidence. The sample in this study is 269 individuals who work as entrepreneurs, police officers, government employees and private employees in major cities in Indonesia areas. Research hypothesis testing was performed using ANOVA statistical tests and was proceeded using IBM SPSS Statistics software version 21. There are six hypotheses proposed in this study and all proposed hypothesis were statistically supported. In other words, there are significant differences in the average value of entrepreneurial characteristics being assessed, among police officers, government employees, private employees, and entrepreneurs. Theoretically, this study will hopefully contribute to invigorating previous studies which provide the evidence of different entrepreneurial characteristics between entrepreneurs and non-entrepreneurs. Practically, the implications of this study can provide suggestions for the personal development in a variety of jobs, especially in terms of entrepreneurial characteristics development. Entrepreneurial characteristics amongst active employees can generate organizational performance improvement. As for the retired employees, entrepreneurial characteristics will be a valuable source in starting a business activity.